Determinant of Fisherman’s Income in Kedung Subdistrict Jepara Regency - Sutijah, Sutijah; Dian Wisika Prajanti, Sucihatiningsih; Muhsin, Muhsin (Universitas Negeri Semarang, 2020)
This study aims to analyze the influence of fishing technology on income through fishermen market access in Kedung Subdistrict Jepara Regency, analyze the effect of fishing capital on income through fishing market access in Kedung Subdistrict Jepara Regency, and analyze the effect of fishing experience on income through fishermen market access in Kedung Subdistric Jepara Regency. The approach used in research is quantitative with quantitative descriptive research methods. The data source was chosen using thetechnique Simple Random Sampling. Data collection techniques were carried out by questionnaire. The analysis technique used is path analysis and sobel test. The results showed that fishing technology influences the income of fishermen through market access of 3,749> 1.91, capital of sea does not affect income through market access with a coefficient of -0.515 <1.91, and experience of sea affects the income of fishermen through market access of 3,193> 1.91